69th meeting of the American Chemical Society, April, 1925 - American Chemical Society (1925)
Panoramic photograph of the Members of the American Chemical Society (ACS) at Aberdeen Proving Ground (APG) as guests of the Army Ordnance Department. On April 9th, 1925, members of ACS visited APG to see chemical and explosive developments since World War I. Aberdeen Proving Ground (APG) is a U.S. Army facility located near Aberdeen, Maryland. Established in 1917, APG is the U.S. Army's oldest active proving ground.
Keywords: Maryland--Aberdeen Proving Ground; Proving grounds; American Chemical Society; Congresses and conventions; Photography, Panoramic